2017
DOI: 10.1007/s10067-017-3541-9
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and reduced physical function go hand in hand in adults with rheumatoid arthritis: a US observational cohort study

Abstract: Objective Reduced physical function and health-related quality of life are common in Rheumatoid Arthritis (RA), and further studies are needed that examine novel determinates of reduced physical function in RA. This study examines whether frailty, a state of increased vulnerability to stressors, is associated with differences in self-reported physical function among adults with RA. Methods Adults from a longitudinal RA cohort (n=124) participated in the study. Using an established definition of frailty, indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 41 publications
3
58
0
5
Order By: Relevance
“…In our RA population, hand grip strength [ 40 , 41 ] and knee extensor strength [ 42 ] were markedly lower than the normative values in the general population. A recent study on frailty and physical function in RA patients [ 43 ] revealed a lower than average hand grip strength and a similar level of knee extensor strength; however, the study population was slightly older, but the percentage of women was similar. Another study [ 44 ] reported similar values for hand grip strength and knee extensor strength in RA patients in remission.…”
Section: Discussionmentioning
confidence: 92%
“…In our RA population, hand grip strength [ 40 , 41 ] and knee extensor strength [ 42 ] were markedly lower than the normative values in the general population. A recent study on frailty and physical function in RA patients [ 43 ] revealed a lower than average hand grip strength and a similar level of knee extensor strength; however, the study population was slightly older, but the percentage of women was similar. Another study [ 44 ] reported similar values for hand grip strength and knee extensor strength in RA patients in remission.…”
Section: Discussionmentioning
confidence: 92%
“…Multivariable logistic regressions were performed to evaluate the cross-sectional relationship between CVD (any CVD and specific CVDs) and other factors known to be associated with frailty: chronic lung disease[ 25 , 26 ], arthritis[ 25 , 27 , 28 ], cancer[ 29 ], diabetes[ 25 ], urine incontinence[ 30 ], and polypharmacy[ 31 ]. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated for the frail compared with the non-frail.…”
Section: Methodsmentioning
confidence: 99%
“…There is considerable literature demonstrating that frail older people tend to have poorer general health and function . However, frailty per se is associated with some diseases (such as depression and dementia) but not others, suggesting that the nature of frailty has not yet been completely characterised .…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable literature demonstrating that frail older people tend to have poorer general health and function. [16][17][18][19][20][21] However, frailty per se is associated with some diseases (such as depression and dementia) but not others, suggesting that the nature of frailty has not yet been completely characterised. 22 For example, what aspects of oral health are worse in frail, compared to non-frail, older people and what are the relationships between various general health comorbidities, frailty and oral health?…”
Section: Introductionmentioning
confidence: 99%